The influence of sales growth, fixed asset intensity, inventory intensity, and firm size on the cash effective tax rate - Pebriani, Rapika; Kasir, Kasir (Institute of Accounting Research and Novation (IARN), 2024)
This research examines the influence of Sales Growth, Fixed Asset Intensity, Inventory Intensity, and Firm Size on the Cash Effective Tax Rate in food and beverage subsector manufacturing companies listed on the IDX in 2015-2022. Descriptive analysis shows variations in Cash Effective Tax Rate, Sales Growth, Fixed Asset Intensity, Inventory Intensity, and Firm Size among these companies. Partially, the analysis results show that Sales Growth, Fixed Asset Intensity, Inventory Intensity, and Firm Size do not have a significant effect on the Cash Effective Tax Rate. However, a very weak relationship was found between each independent variable and the Cash Effective Tax Rate. Simultaneously, the four independent variables also do not have a significant effect on the Cash Effective Tax Rate, with a coefficient of determination value of 4.3%, indicating that 95.7% of the variation in the Cash Effective Tax Rate is influenced by other factors. Thus, this research concludes that Sales Growth, Fixed Asset Intensity, Inventory Intensity, and Firm Size do not have a significant influence on the Cash Effective Tax Rate in food and beverage subsector manufacturing companies on the IDX during the 2015-2022 period, indicating that there are other factors that are more important. dominantly influences the Cash Effective Tax Rate.